STRATEGI PENGEMBANGAN EKONOMI KOMUNITAS NELAYAN DI DESA MAITARA SELATAN KECAMATAN TODORE UTARA, KOTA TIDORE KEPULAUAN, PROVINSI MALUKU UTARA - Suhardi, Suhardi (EDUTECH CONSULTANT, 2018)
The development strategy of Economic Community of Fishermen in the Village of South Maitara, Sub District of North Tidore, Province of North Maluku. Marine fishery resources is a resources potential for economic development and wii-being of coastal communities, especially fishermen. To achieve these objectives be effectively and efficiently we need a strategy. This research was conducted in the village of South Maitara, District of North Tidore, Tidore Island, North Maluku Province. The sample is this study was 21 fishermen. The data used are secondary and primary data and are analyzed using SWOT analysis. The results showed that the economic development of fishermen still can be done by implementing the following strategies: (1). Increase the number of and quality of fishing equipment (2). Improving the quality of human resources through training (3). Improve the quality of facilities and infrastructure (4). Increased access to financing from financial institutions, and (5). The government’s policy of pro fishermen and the quality of natural resources.